2020
DOI: 10.17221/360/2018-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, microbial and antioxidant activity of Cola lepidota K. Schum fruits

Abstract: This research was to investigate the chemical composition, antioxidant activity, and microbial profiles of Cola lepidota fruits. One hundred grams each of the fruit exocarp, mesocarp and endocarp were blended and analyses were carried out by the following standard methods. Active acidity and vitamin C contents were 5.5 and 6.34 mg 100 g<sup>–1</sup> in endocarp, 4.5 and 14.39 mg 100 g<sup>–1</sup> in mesocarp and 6.7 and 10.02 mg 100 g<sup>–1</sup> for exocarp. Moisture and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(23 reference statements)
1
1
0
Order By: Relevance
“…This trend was also confirmed by Okudu et al [34], who reported the presence of these phytochemicals -flavonoids, saponins, phenols and tannins. Also, Oranusi, et al [30] and Ene-Obong et al [34] corroborated the result from this study. The authors reported that flavonoid and βcarotene are the most abundant phytochemicals in Cola lepidota fruits.…”
Section: Phytochemical Composition Of C Lepidotasupporting
confidence: 89%
See 1 more Smart Citation
“…This trend was also confirmed by Okudu et al [34], who reported the presence of these phytochemicals -flavonoids, saponins, phenols and tannins. Also, Oranusi, et al [30] and Ene-Obong et al [34] corroborated the result from this study. The authors reported that flavonoid and βcarotene are the most abundant phytochemicals in Cola lepidota fruits.…”
Section: Phytochemical Composition Of C Lepidotasupporting
confidence: 89%
“…The values obtained in this study was higher than those of Udouroso and Essien, [17] who reported that C. lepidota contained high amount of vitamin B 1 (0.249 mg/100 g), B 2 (0.125 mg/100 g), B 3 (0.940 mg/100 g) and Vitamin C (6.497 mg/100 g). Oranusi et al [30] also reported that the vitamin C content was 14.39 mg/100 while Ogbu and Umeokechukwu [1] reported the vitamin C content was 13.47 mg/100 g for Cola lepidota.…”
Section: Vitamin Composition Of C Lepidotamentioning
confidence: 98%